2010
DOI: 10.1093/eurheartj/ehq245
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and prognostic value of pulmonary arterial pressure in patients with chronic heart failure

Abstract: Using a definition of PASP > 45 mmHg, 7% of the patients with HF have PAH, which is associated with worse LV function, MR, and prognosis. Whether PAH is a target for therapy in this population remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 25 publications
10
110
4
2
Order By: Relevance
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in this analysis are Valerio et al,10 Heresi et al,11 Kovacs et al,5 Suzuki et al,12 Maron et al,3 Takahashi et al,13 Douschan et al,4 Assad et al,2 Abramson et al,14 Kjaergaard et al,15 Shalaby et al,16 Lam et al,17 Damy et al,18 Cabrita et al,19 and Choudhary et al 20. CI indicates confidence interval; M‐H, Mantel‐Haenszel; RHC, right heart catheterization.…”
Section: Resultsmentioning
confidence: 99%
“…Even though most of patients qualified to HTx have pulmonary artery hypertension, some authors underline neutral influence of PH on their prognosis [12,13]. A possible explanation for this observation is that patients on the waiting list to HTx are highly selected, homogenous with terminal HF, thus limiting the chances for identifying differences.…”
Section: Discussionmentioning
confidence: 99%
“…18 Other common techniques used are DTI derived s´ wave velocity, fractional area change and Tei index (which also evaluates diastolic function).…”
Section: Right Ventricular Functionmentioning
confidence: 99%